Hubungan Antara Interaksi Peer Group dengan Kecemasan di Kalangan Siswa Kelas XI SMA Negeri 1 Mengwi Tahun 2026 - Ni Putu Dewi Yuliantari; I Wayan Susanta; I Made Mahaardhika (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aimed to determine the relationship between peer group interaction and anxiety among eleventh-grade students of SMA Negeri 1 Mengwi in 2026. This study employed a quantitative approach with a correlational design. The population consisted of 498 eleventh-grade students, with a sample of 222 students selected using the Slovin formula and Proportionate Stratified Random Sampling technique. Data were collected using peer group interaction and anxiety questionnaires that had met validity and reliability requirements. Data analysis was conducted using descriptive statistics, normality test, linearity test, and Pearson Product Moment correlation test with the assistance of SPSS version 27.0. The results revealed a significant negative relationship between peer group interaction and students' anxiety, with a correlation coefficient of r = -0.621 and a significance value of 0.000. The correlation was categorized as strong, indicating that better peer group interaction was associated with lower levels of anxiety among students. Peer group interaction contributed 38.5% to students' anxiety, while the remaining 61.5% was influenced by other factors beyond the scope of this study. Therefore, peer group interaction plays an important role in reducing students' anxiety within the school environment.